The Implementation of Environmental Management Accounting and Sustainable Tourism in Tourism Villages in Bali - Sang Putu Eka Pertama; I Putu Astawa; I Gede Mudana (International Journal of Glocal Tourism, 2022)
Purpose: This study aims to analyze the implementation of sustainable tourism based on environmental management accounting in tourism villages in Bali, Indonesia. Research methods: This research method is qualitative which data collection techniques were done through documentation studies. This method was chosen to gain a deep understanding of the implementation of sustainable tourism based on environmental management accounting in tourism villages in Bali. Findings: The participation of tourism actors in implementing sustainable tourism based on environmental management accounting in tourism villages in Bali is still not maximized. Implications: The process of community empowerment to open accommodation services in the form of homestays that use the principles of green tourism, local transportation services, the availability of craft and art communities, and local guides is still very rare.